Implementasi Kebijakan Pengembangan Kawasan Agropolitan Di Kabupaten Lamongan - Ayudya Fitria Mazdalifa (Jurnal Administrasi Publik, 2013)
Abstract: The Implementation of Regional Agropolitan Development Policy in Lamongan. Lamongan regency government implemented agriculture-based development that was implemented in the form of regional Agropolitan development policies. The policy was launched in 2008 in order to reduce the development gap between the north and south region in Lamongan through the development of agricultural potential. After five years of implementation, the policy was interesting to study the progress of the implementation and impact as well as how the public response to the policy. This research used descriptive qualitative research methods. The results of this research was the implementation of regional Agropolitan development policy gradually was developed normatively both policy and operations. It was shown by an increase in realization of activities and the allocation of funds in the year 2010 to 2012. Some short comings in the implementation of social policy was the lack of local government for the low response communities, yet the maximum coordination between local government actors, and the lack of SOPs as guidelines for SKPDs. It results in the implementation of regional Agropolitan development policies was not seriously affected by the changes in the south region of Lamongan. So the government should encourage more socialization and maximize the coordination, especially between education and development as soon as possible was made SOP in Agropolitan region. Keywords: Implementation of Policies, Policy Development of Agropolitan Region  Abstrak: Implementasi Kebijakan Pengembangan Kawasan Agropolitan di Kabupaten Lamongan. Pemerintah Kabupaten Lamongan melaksanakan pembangunan berbasis pertanian yang diimplementasikan dalam bentuk kebijakan pengembangan kawasan Agropolitan. Kebijakan tersebut dicanangkan pada tahun  2008 guna mengurangi kesenjangan pembangunan antara wilayah utara dan selatan Kabupaten Lamongan melalui pengembangan potensi pertanian. Setelah lima tahun diimplementasikan, kebijakan tersebut menjadi menarik untuk dikaji sejauh mana perkembangan implementasi dan dampaknya serta bagaimana respon masyarakat terhadap kebijakan tersebut. Penelitan ini menggunakan metode penelitian kualitatif deskriptif. Hasil dari penelitian ini adalah implementasi kebijakan pengembangan kawasan Agropolitan mengalami perkembangan secara bertahap baik secara normatif  kebijakan maupun kegiatannya. Hal tersebut ditunjukkan dengan adanya peningkatan realisasi kegiatan dan alokasi dana pada tahun 2010 hingga 2012. Beberapa kekurangan dalam  implementasi kebijakan tersebut adalah minimnya sosial dari pemerintah daerah yang menyebabkan rendahnya respon masyarakat, belum maksimalnya koordinasi antaraktor pemerintah daerah, dan belum adanya SOP sebagai pedoman bagi SKPD. Hal tersebut menjadikan implementasi kebijakan pengembangan kawasan Agropolitan belum berdampak secara signifikan terhadap perubahan di wilayah selatan Kabupaten Lamongan. Sehingga pemerintah daerah harus lebih menggalakkan sosialisasi, memaksimalkan koordinasi terutama antarSKPD serta sesegera mungkin dibuat SOP pengembangan kawasan Agropolitan. Kata kunci: Implementasi Kebijakan, Kebijakan Pengembangan Kawasan Agropolitan